Stop bush fires! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The President of the Ghana Wildlife Society at the Kumasi National University of Science and Technology in Ghana, Mr Abotsi Anselm, told us of his group s appeal to all concerned parties to avoid bush fires at the critical period early in 2001. In...